Stockholm Convention Flame Retardant Emissons from Selected E-Waste Processing Facilities in Turkey - Odabasi, Mustafa; Kurt-Karakus, Perihan Binnur; Birgul, Askin; Dumanoglu, Yetkin; Kara, Melik; Akcetin, Merve Ozkaleli; Syed, Jabir (Mehmet Sinan Bilgili, 2022)
E-waste processing facilities are hot spots for several chemicals to the environment including flame retardants. The current study investigates certain brominated flame retardants (FRs) emissions to air from selected waste electrical and electronic equipment (WEEE) processing facilities in Turkey by employing passive air sampling technique. As WEEE has been recognized as a potential source of contaminants including flame retardants to the environment, severe environmental pollution and human health problems may arise from these sites if such wastes are not recycled properly. Researches conducted in other parts of the world reported extremely high concentrations of PBDEs in soil, dust, air and biological samples collected nearby WEEE processing facilities. As a signatory to the Stockholm Convention, which is an international agreement to protect human and environmental health from the adverse effects of persistent organic pollutants (POPs) including certain brominated flame retardants, Turkey is obliged to perform improved monitoring and characterization of POPs sources to the environment. As the turnover of WEEE in waste management facilities has grown rapidly in recent years, we think such facilities may act as hot spots of FRs emissions to air. To the authors' best knowledge, the current study aiming to determine the emissions of selected organic brominated FRs to the air from licensed WEEE processing facilities is the first study in Turkey to investigate such an environmental pollution status.
6th EurAsia Waste Management Symposium (EWMS) -- OCT 24-26, 2022 -- Istanbul, TURKEY
Keywords: waste electric and electronic equipment (WEEE); e-waste processing; Stockholm Convention flame retardants (POP-FRs); air; passive sampling